IMPLEMENTATION OF I'DAD CLASS AS THE FOUNDATION OF EDUCATION IN ISLAMIC-BASED CHILD-FRIENDLY SCHOOLS - Maharani, Okvi; Wahyudi, Andik Sugeng (PT. Antis International Publisher, 2025)
Objective: Objective: This research aims to explore the implementation, challenges, and impacts of the I'dad program in Madrasah Ibtidaiyah (MI) based on the principles of Child-Friendly Schools and Islamic values. Method: The research method uses a qualitative approach with case studies, involving in-depth interviews, participatory observations, and document analysis. Result: The results of the study show that the program focuses on students' academic, social, and emotional readiness through individual and classical approaches and multisensory learning methods. Islamic values such as prayer before study and patience are integrated into daily activities. This program has succeeded in improving students' reading, writing, and motor skills, as well as building Islamic character. However, challenges such as limited media, therapy spaces, and custom module designs are still faced. Regular evaluation, collaboration with parents, teachers, and psychologists are the key to the success of this program. Novelty: With continuous development, the I'dad program has the potential to become an inclusive education model based on Islamic values to support students' readiness to study in Indonesia.